KAJIAN HADIS DI KAWASAN BASRAH: Sebuah Analisis Tentang Penyebaran dan Perkembangan Hadis di Basrah - Nurul Atik Hamida; Lau Han Sein (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2022)
Basrah is a city that was built at the beginning of the development of Islam around the year 16 H, precisely during the reign of the caliph Umar bin al-Khattab. In the field of science, Basrah is one of the cities visited by many scholars to seek knowledge, including hadith scholars. The purpose of this study was to determine the study of hadith in Basrah City, both in its development and dissemination. This research is a library research with descriptive analysis method. The results of this study indicate that in Basrah there are many figures who teach Islamic knowledge, especially the Qur'an and Hadith. Hadith itself had entered Basrah during the period of Umar bin Khattab's friend, but at this time the hadith was not so developed because Umar chose to be careful in terms of transmitting hadith by doing al-tathabbut wa taqlil min al-riwayah (tightening or limiting the hadith). and reduce the transmission of hadith). In addition, in Basrah there are also a number of sahabat and tabi'in who live so that they become a reference for obtaining a history of hadith. With the many narrators of hadith from the generation of sahabat and tabi'in in this city, it proves that Basrah is included in the city that is used as a rihlah for religious leaders to demand or spread knowledge Basrah merupakan kota yang dibangun pada awal perkembangan Islam sekitar tahun 16 H, tepatnya pada masa pemerintahan khalifah Umar bin al-Khattab. Dalam bidang keilmuan, Basrah menjadi salah satu kota yang banyak di datangi para ulama untuk mencari ilmu termasuk para ulama hadis. Tujuan dari penelitian ini adalah untuk mengetahui kajian hadis di Kota Basrah, baik dalam perkembangan dan penyebaranya. Penelitian ini merupakan penelitian kepustakaan dengan metode anasis deskriptif. Hasil penelitian ini menunjukkan bahwa di Basrah banyak para tokoh yang mengajarkan ilmu keislaman, terutama al-Qur’an dan Hadis. Hadis sendiri sudah masuk ke Basrah pada masa periode sahabat Umar bin Khattab, akan tetapi pada masa ini hadis tidak begitu berkembang karena Umar memilih bersikap hati-hati dalam hal periwayatan hadis dengan melakukan al-tathabbut wa taqlil min al-riwayah (memperketat atau membatasi hadis dan mempersedikit periwayatan hadis). Selain itu, di Basrah juga terdapat sejumlah sahabat dan tabi’in yang berdomisili sehingga menjadi rujukan untuk mendapatkan sebuah riwayat hadis. Dengan banyaknya para perawi hadis dari generasi sahabat dan tabi’in di kota ini, membuktikan bahwa Basrah termasuk ke dalam kota yang dijadikan rihlah para tokoh Agama untuk menuntut atau menyebarkan ilmu.